Airborne lidar observations in the wintertime Arctic stratosphere - Polar stratospheric clouds - Browell, E. V.; Ismail, S.; Carter, A. F.; Higdon, N. S.; Butler, C. F.; Robinette, P. A.; Toon, O. B.; Schoeberl, M. R. (1990)
Polar stratospheric cloud (PSC) distributions in the wintertime Arctic stratosphere and their optical characteristics were measured with a multiwavelength airborne lidar system as part of the 1989 Airborne Arctic Stratospheric Expedition. PSCs were observed on 10 flights between January 6 and February 2, 1989, into the polar vortex. The PSCs were found in the 14-27 km altitude range in regions where the temperatures were less than 195 K. Two types of aerosols with different optical characteristics (Types 1a and 1b) were observed in PSCs thought to be composed of nitric acid trihydrate. Water ice PSCs (Type 2) were observed to have high scattering ratios (greater than 10) and high aerosol depolarizations (greater than 10 percent) at temperatures less than 190 K.